Penerapan Metode RAD Pada Aplikasi Manajemen Perpustakaan Sekolah Dasar Nasional Amanah Bangsa Berbasis Web - Gustiansyah, Ahmad Rizqi; Wiyanto, Wiyanto; Zy, Ahmad Turmudi (STMIK Banjarbaru, 2024)
Among the elements of education, the library emerges as a focal point in leveraging technology to enhance access, efficiency, and quality of services. At SD Nasional Amanah Bangsa, library data processing is still performed manually by staff, who record the book list conventionally without the support of data processing programs. This situation leads to a lack of transparency in monitoring book borrowing and returns, hindering the library management's ability to make accurate decisions. To address this issue, this study proposes the implementation of a web-based library management system using the Rapid Application Development (RAD) method with the integration of barcode technology. The RAD method allows for rapid and responsive software development, while barcodes enhance recording efficiency and accuracy. The implementation of this system is expected to expedite administrative processes, reduce manual errors, and improve transparency and the quality of library services. System testing results show that all main functions were successfully implemented, with testing results indicating a